Numerical simulation of hydraulic force on the impeller of reversible pump turbines in generating mode - 李金伟 张宇宁 刘凯华 冼海珍 于纪幸 (Journal of hydrodynamics. Series B, 2017)
The hydraulic force on the reversible pump turbine might cause serious problems（e.g., the abnormal stops due to large vibrations of the machine）, affecting the safe operations of the pumped energy storage power plants. In the present paper, the hydraulic force on the impeller of a model reversible pump turbine is quantitatively investigated through numerical simulations. It is found that both the amplitude of the force and its dominant components strongly depend on the operating conditions（e.g., the turbine mode, the runaway mode and the turbine brake mode） and the guide vane openings. For example, the axial force parallel with the shaft is prominent in the turbine mode while the force perpendicular to the shaft is the dominant near the runaway and the turbine brake modes. The physical origins of the hydraulic force are further revealed by the analysis of the fluid states inside the impeller.